An evaluation of Online Training Effectiveness and Pre-Service and In-Service Teacher Satisfaction: A Case Study from Nigeria - Mohebi, Laila Murtadha Baqer; AlShamsi, Alanood; AlHammadi, Mariam; AlMohsen, Fatima (MO.RI Publishing, 2023)
This study evaluates the perceptions of 122 pre-service and in-service Nigerian teachers on adopting an online training module during the COVID-19 pandemic, a period marked by significant educational challenges and shifts. Employing a qualitative approach through open-ended online questions, it delves into the factors critical to enhancing online training effectiveness. Key findings highlight the importance of training in imparting theoretical knowledge and practical skills, the quality and relevance of content, interactivity, practical examples, and appropriate video length. These align with existing literature, underscoring the effectiveness of online training in challenging times. Significantly, nearly all participants expressed satisfaction with the training. This research not only sheds light on effective online teaching strategies but also offers practical recommendations for the continuous improvement of teacher training in Nigeria.